2019
DOI: 10.1017/s2040174419000503
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational effects of chronic maternal exposure to a high sugar/fat diet and physical training

Abstract: Pregnant individuals who overeat are more likely to predispose their fetus to the development of metabolic disorders in adulthood. Physical training is a prevention and treatment interventional strategy that could treat these disorders, since it improves metabolism and body composition. This study assessed the protective effect of physical exercise against possible metabolic changes in generations F1 and F2, whose mothers were subjected to a high-sugar/high-fat (HS/HF) diet. Wistar rats belonging to generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…2017, 2019; Martins Terra et al . 2019). In addition, a HSHF diet during gestation induces hyperinsulinaemia, hyperglycaemia and glucose intolerance in the mother (Sferruzzi‐Perri et al .…”
Section: Introductionmentioning
confidence: 99%
“…2017, 2019; Martins Terra et al . 2019). In addition, a HSHF diet during gestation induces hyperinsulinaemia, hyperglycaemia and glucose intolerance in the mother (Sferruzzi‐Perri et al .…”
Section: Introductionmentioning
confidence: 99%
“…A recent animal study examined the multigenerational effect of physical activity in pregnant rats, and found that prenatal exercise reduced adiposity and glucose concentrations in offspring up to three generations later compared to rats that were sedentary throughout gestation (Martins Terra et al 2020). Limited research has evaluated the effect of exercise during pregnancy on cord blood leptin levels and adipocytes in human models.…”
Section: Exercise and Pregnancy Prevents Disease Risk R113mentioning
confidence: 99%
“…Furthermore, exercise during pregnancy lowers the risk of children being born LGA and decreases neonatal fat mass 13 . Numerous rodent studies have also shown positive long term effects of maternal exercise on offspring metabolic health such as prevention of obesity and diabetes 14 , with protection lasting up to three generations after maternal exercise was imposed 15 . The mechanisms by which exercise stimuli affect developmental programming are not fully established, but the placental-foetal system is thought to play a central role 14 .…”
Section: Introductionmentioning
confidence: 99%